Restorative Justice im Strafvollzug im europäischen Vergleich - Dünkel, Frieder; Lehmkuhl, Marianne Johanna; Păroşanu, Andrea (Über Mauern blicken - 25 Jahre Forschen im Justizvollzug: Festschrift für Ueli Hostettler zum 65. Geburtstag, 2025)
Restorative justice is increasingly becoming the focus of European criminal law policy. This article takes a comparative look at the legal, political, and institutional frameworks for integrating restorative approaches into the penal system. Examples from various European countries show how far developments have progressed—from model initiatives to a lack of structural anchoring. The article argues that restorative justice should not be seen merely as a supplementary measure, but as an integral part of a human rights-oriented and sustainable penal system. This requires not only legal and organizational reforms, but also an interdisciplinary debate on attitudes, institutional conditions, and long-term objectives of the penal system in Europe. (machine translation)